Incidencia del cuidado del medio ambiente en la formación de valores para el desarrollo social del educando del nivel inicial de la Escuela Francisco Huerta Rendón del cantón Babahoyo Provincia de Los Ríos - Zambrano Toaza, Nathaly Milena (2023)
Caring for the environment is everyone's responsibility, which is why parents, teachers and the community are responsible for the education of children, instilling values that allow their social development, therefore loving and caring for the environment in which educational institutions have a relevant role. Participation when carrying out activities that allow the development of awareness in children and thus contribute to the environment. For this reason, the need to carry out the following investigation is felt, which allows Analyzing the incidence of Environmental Care, the objective is to use environmental theories as a tool in the Formation of Values for the social development of the student, the methodology used is non-experimental descriptive, in the data collection the survey was used to 35 parents of the Institution the data obtained from the study demonstrate the need to take care of the environment and the importance that this has to help in the formation of values and social development of the students in which it has been concluded that the environment can be implemented as a guide because it allows the development of different values skills, education being the main entity to promote care for the environment from the classroom.